2010
DOI: 10.1586/edm.10.25
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in immunosuppressed patients

Abstract: The immunogenic characteristics of malignant melanoma are intriguing. To date, multiple studies exist regarding the immunogenicity of melanoma. In this article, we summarize data in the literature on the role of immunosuppression in melanoma and discuss several immunocompromised patient populations in detail. A comprehensive PubMed search was conducted with no date limitation. The following search terms were used: melanoma in combination with immunosuppression, immunocompromised, genetics, antigen processing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…However, several studies have reported no deaths due to melanoma in cases of malignant melanoma in situ or thin superficial spreading melanoma in the organ transplant recipients. 29,34,44,52 In a recent European multicenter retrospective study of 100 melanomas (91 occurred 25 ); others have not found a significant difference. 6 Other factors found to correlate with increased risk of melanoma included use of T lymphocyte-depleting antibodies and excessive UV radiation exposure.…”
Section: Clinical Course Of Melanoma In Solid Organ Transplant Recipimentioning
confidence: 99%
See 4 more Smart Citations
“…However, several studies have reported no deaths due to melanoma in cases of malignant melanoma in situ or thin superficial spreading melanoma in the organ transplant recipients. 29,34,44,52 In a recent European multicenter retrospective study of 100 melanomas (91 occurred 25 ); others have not found a significant difference. 6 Other factors found to correlate with increased risk of melanoma included use of T lymphocyte-depleting antibodies and excessive UV radiation exposure.…”
Section: Clinical Course Of Melanoma In Solid Organ Transplant Recipimentioning
confidence: 99%
“…In addition, we elaborate on the clinical scenarios of patients with a history of melanoma before transplant and melanoma that resulted from transmission from the organ donor. 25 De Novo Melanoma Posttransplant Solid organ transplant recipients have an increased risk of many malignant neoplasms, with skin cancer being the most common, affecting 50% or more of these patients. 26 The exact incidence of de novo melanomas posttransplant continues to be in question.…”
Section: Article Highlightsmentioning
confidence: 99%
See 3 more Smart Citations